Answer:
JL=3x
Step-by-step explanation:
JL=5x+2
-2. -2
JL=3x
Answer:
f(x) = x² +x -6
Step-by-step explanation:
The standard form will look like ...
f(x) = x² +bx +c
where b is the opposite of the sum of the roots, and c is their product.
f(x) = x² -(-3+2)x +(-3)(2)
f(x) = x² +x -6
_____
<em>Additional comment</em>
In general, "standard form" is ax²+bx+c. In this case, the coefficient 'a' can be 1 since neither of the roots is expressed as a fraction. The sum of roots is (-b/a) and the product of roots is (c/a).
9514 1404 393
Answer:
32.9
Step-by-step explanation:
The ratio of long side to hypotenuse is the same for all of the triangles in the figure.
AD/AB = AB/AC
AB^2 = AD·AC = 30·36
AB = 6√30 ≈ 32.863
To the nearest tenth, AB ≈ 32.9.
Answer:
A
Step-by-step explanation:
u can just test them out